The effect of intellectual capital and networking on the organizational values of Islamic Boarding Schools (A case study on Khalaf Islamic Boarding Schools in Demak) - Sari, Alifah Ratna; Prasetyoningrum, Ari Kristin; Hartono, Setyo Budi (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - This study aims to determine the effect of intellectual capital and networking on the organizational values of Islamic boarding schools seen from the resources they have.Method - The population in this study is the khalaf Islamic boarding schools in Demak Regency. The sampling technique is done by purposive sampling which is a sample selection technique using certain criteria or considerations. Samples taken as many as 40 boarding schools. Data testing is done by SEM-PLS and processed using the WarpPLS 5.0 program.Result - The analysis shows that intellectual capital has a positive and significant effect on the organizational values of Islamic boarding schools as evidenced by a positive path coefficient (0.306) and a significance value 0.05 (P-value 0.017). Likewise, the network has a positive and significant effect on the organizational values of Islamic boarding school as evidenced by a positive path coefficient (0.324) and a significance value 0.05 (P-value 0.012).Implication - It is expected that khalaf Islamic boarding schools will pay attention to the importance of intellectual capital, both from human capital, structural capital and relational capital and networking to improve organizational values but not to erase the classical boarding school tradition.Originality - The originality of this study is the object of the research. If previous researches conducted research on economic and banking organizations, this research used Islamic education organizations (khalaf Islamic boarding schools) as the object of research.